AREA OPTIMALIZATION WITH SYSTEMATIC LAYOUT PLANNING AND CLASS BASED STORAGE METHODS TO INCREASE STORAGE CAPACITY - Merjani, Abdullah; Mulyadi, Dede (SIGMA TEKNIKA, 2023)
PT Simatelex Manufactory Batam (SMB) is engaged in Coffee Maker and Pizza Maker. In the manufacture of these products, they are divided into several buildings in the Batamindo Industrial Park area, the products produced are made based on orders from customers. The products produced by the company are mostly marketed abroad (exports). In the production of Coffee Maker which is located on Jl. Beringin Muka Kuning, Lot 003, Batamindo Industrial Park Area, Batam. Finished products are then stored in the warehouse area on the ground floor of the building (Ground) which has an area capacity of 60%, so that all finished goods cannot be stored, in addition to using an area of 60%, another cause of finished goods not being able to be stored is all mismatched placement. finished goods include Finished Goods Fresh from the production line and Finished Goods to Shipping, so that there are no finished goods to shipping sequences that are not in accordance with CO (Create Order) and there is a buildup of products in the finished goods area. Therefore, the authors are interested in conducting research by anticipating these conditions so that it is necessary to optimize the storage of the finished goods. Improvements made in the form of changes to the flow of finished goods moving, re-layout the optimal warehouse stock level using the Systematic Layout Planning method, and making verbal control monitoring in the warehouse using the Class Based Storage method. From these improvements, the results obtained are an increase in area use by 60% to 80%, and also ensure that the area capacity can meet the company's needs.